30 Lack of specialist involvement in heart failure diagnosis leave concerning gaps in management: an all ireland analysis. (7th October 2015) - Monaghan, M; Travers, B; Kinsella, M; Gallagher, J; O'Connell, E; Watson, C; O'Hanlon, R; Ledwidge, M; Mailey, J; Henderson, JA; Dixon, L; McDonald, K
Abstract : Purpose: Previous research has identified that patients with a diagnosis of heart failure in the community frequently have not had previous heart failure specialist assessment. This study sought to determine the characteristics of patients with a label of heart failure in the community without a record of previous specialist assessment in two different health systems. Methods: Patients with a coded diagnosis of heart failure or on loop diuretics were identified in 13 general practice electronic health records in the Republic of Ireland and Northern Ireland. Records were reviewed and data was extracted on those patients who had no previous record of cardiology specialist assessment. Results: 111 patients met the criteria for inclusion. The demographic details are outlined in Table 1 . Patients with a diagnosis of heart failure in the community without previous specialist assessment tended to be older females with low levels of recent echocardiography. Use of natriuretic peptide testing was low in both healthcare systems. Loop diuretic use was high despite a low rate of echocardiography and lack of specialist assessment. Conclusion: This All-Ireland cohort of patients with a diagnosis of heart failure in the community or who are on heart failure medication have not had specialist assessment. The use of loop diuretic is high with low rates of Echocardiography. The lack of echocardiography means it is not possible to determine if patients with heart failure have HF-REF or HF-PEF. Strategies to reach this patient group need to be developed to confirm diagnosis and implement appropriate medical and device management.